A faster pixel-decimation method for block motion estimation in H.264/AVC - Lins, Robson; Henriques, Diogo; Lima, Emerson; Melo, Sílvio (Trends in Computational and Applied Mathematics, 2014)
This work explores the highly advantageous cost/benefit relation presented by low discrepancy sequences as a pixel-decimation technique to improve the block estimation performance  in the H.264/AVC. The proposed method is able to efficiently estimate motion vectors for block matching algorithms present in the H.264 by using latticed decimation sampled according to the Van Der Corput-Halton sequences. This paper further explores motion estimation within the H.264, validating it with real-case-video-encoding scenarios. The results have shown that this technique  incorporated to the H.264 is generally more efficient than other decimation techniques used in similar conditions.